2010
DOI: 10.1016/j.otohns.2009.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Screening for obstructive sleep apnea/hypopnea syndrome: Subjective and objective factors

Abstract: Neither the Berlin questionnaire nor the OSAHS score alone was both highly sensitive and specific for diagnosing OSAHS. By incorporating subjective and objective metrics into a single predictive equation, sensitivity and specificity were maximized, and 82.5 percent of diagnoses were accurately predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
0
27
0
2
Order By: Relevance
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of individuals suspected to have OSA, the sensitivity of the OSAS score was 0.86 (95% CI: 0.80 to 0.91) against PSG at an AHI > 5 cut = off, however; specificity was lower at 0.47 (95% CI: 0.34 to 0.56) with a high number of false positives in the low-risk group 39 (see supplemental material, Table S35). One study evaluating the performance of the Kushida Index against PSG showed a high sensitivity of 0.98 (95% CI: 0.95 to 0.99) and high specificity of 1.00 (95% CI: 0.92 to 1.00) to detect AHI ≥ 5 (see supplemental material, Table S36).…”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
“…The PSGs were performed according to commonly accepted clinical standards. 15,16 The montage included encephalogram leads O1A2, O2A1, C1A2, C2A1, F1A2, F2A1; electromyogram leads for left eye, right eye, submentalis, and leg (left and right separately), electrocardiogram, and respiratory status measures by nasal airflow (nasal air pressure) and oronasal airflow (thermistor, used for backup), rib cage and abdominal respiratory effort (respiratory impedance plethysmographs), and pulse oximetry. Sleep scoring was done in 30-sec epochs according to the system of Rechtschaffen and Kales, 17 as modified by the 2007 AASM scoring manual.…”
Section: Polysomnographymentioning
confidence: 99%
“…При этом, если само отчеты о храпе могут быть достаточно надежными, то данные об остановках дыхания во сне, повиди мому, менее точны и нуждаются в дополнительной верификации [15]. Вместе с тем, настоящее исследо вание и его результаты отвечают задачам скрининга и позволяют определить перспективные направления для дальнейших изысканий.…”
Section: Discussionunclassified